Colorimetric determination of xanthine with xanthine oxidase and WSe2 nanosheets as a peroxidase mimic. (25th May 2021) - Hong, Chengyi; Guan, Lingyan; Huang, Lei; Hong, Xiaoshan; Huang, Zhiyong
Abstract : A colorimetric method combining WSe2 nanosheets with peroxidase-like activity and xanthine oxidase was developed for xanthine detection in serum samples. Abstract : A colorimetric method combining WSe2 nanosheets with peroxidase-like activity and xanthine oxidase (XAO) was developed for xanthine detection. XAO catalyzes xanthine oxidation and thereby induces H2 O2 production. WSe2 nanosheets can catalyze the oxidization of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) by H2 O2 and produce a blue oxidation product of TMB (oxTMB). Under optimal conditions, the colorimetric method showed a linear response for xanthine detection in a range of 0.01–0.5 mM. The limit of detection was 4.37 μM. The recovery rate from spiked serum samples was 95.5%–115.5%. Therefore, our strategy provides new opportunities for the detection of xanthine and evaluation of health care.